2006
DOI: 10.1111/j.1529-8817.2006.00193.x
|View full text |Cite
|
Sign up to set email alerts
|

EXTRACELLULAR MATRIX ASSEMBLY IN DIATOMS (BACILLARIOPHYCEAE). V. ENVIRONMENTAL EFFECTS ON POLYSACCHARIDE SYNTHESIS IN THE MODEL DIATOM, PHAEODACTYLUM TRICORNUTUM1

Abstract: The effects of phosphate (P) limitation, varying salinity (5-65 psu), and solid media growth conditions on the polysaccharides produced by the model diatom, Phaeodactylum tricornutum Bohlin were determined. Sequential extraction was used to separate polymers into colloidal (CL), colloidal extracellular polymeric substances (cEPS), hot water soluble (HW), hot bicarbonate soluble (HB), and hot alkali (HA) soluble fractions. Media-soluble polymers (CL and cEPS) were enriched in 4-linked mannosyl, glucosyl, and ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
156
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(169 citation statements)
references
References 75 publications
(207 reference statements)
9
156
1
Order By: Relevance
“…TEP plays an important role in the biogeochemistry of the biological carbon pump (Passow & Carlson, 2012) and consequently there is a need to better define its composition to determine its origin and biogeochemical significance. Much of the recent detailed work on the composition of EPS produced by diatoms has been conducted with laboratory-grown cultures of benthic epipelic diatoms (Underwood et al, 2004;Bellinger et al, 2005;Abdullahi et al, 2006). There is no reason why the techniques used in this research could not be applied to ecologically relevant taxa of phytoplankton.…”
Section: Chemical Characterization Of Dom Released By Phytoplanktonmentioning
confidence: 99%
See 1 more Smart Citation
“…TEP plays an important role in the biogeochemistry of the biological carbon pump (Passow & Carlson, 2012) and consequently there is a need to better define its composition to determine its origin and biogeochemical significance. Much of the recent detailed work on the composition of EPS produced by diatoms has been conducted with laboratory-grown cultures of benthic epipelic diatoms (Underwood et al, 2004;Bellinger et al, 2005;Abdullahi et al, 2006). There is no reason why the techniques used in this research could not be applied to ecologically relevant taxa of phytoplankton.…”
Section: Chemical Characterization Of Dom Released By Phytoplanktonmentioning
confidence: 99%
“…It is probable that an individual phytoplankton strain or species is capable of producing multiple extracellular carbohydrates at the same time. This has been shown for benthic diatoms, whose extracellular carbohydrate production has been extensively studied over the last few years (Underwood & Paterson, 2003;Bellinger et al, 2005Bellinger et al, , 2009Abdullahi et al, 2006). Monosaccharides commonly found in extracellular carbohydrates released by marine phytoplankton include aldohexoses (glucose, galactose and mannose), aldopentoses (arabinose and xylose), deoxysugars (fucose and rhamnose), uronic acids (glucuronic acid) and amino sugars (Aluwihare et al, 1997;Biersmith & Benner, 1998;Aluwihare & Repeta, 1999;Magaletti et al, 2004;Kragh & Søndergaard, 2009).…”
Section: Carbohydratesmentioning
confidence: 99%
“…Adhesion provides traction for the 'gliding' form of motility used by motile pennate diatoms to adjust their position in relation to fluctuating environmental circumstances. The biochemical composition of EPS not only varies between different diatom species, but can also vary depending on the environmental conditions the diatom is being exposed to (Abdullahi et al, 2006). EPS molecules of pennate diatoms are secreted through pores in the frustules and through the slit-like raphe, and recent studies using Atomic Force Microscopy (reviewed in Chiovitti et al, 2006) clearly demonstrate differences in mechanical properties of EPS materials secreted from these two locations.…”
Section: Introductionmentioning
confidence: 99%
“…The complete genome sequence of P. tricornutum will become available soon, along with the first microarrays (Scala et al, 2002;Montsant et al, 2005). Recent studies of the EPS of P. tricornutum have focused on the changes in the biochemical composition under changing environmental conditions (Abdullahi et al, 2006) and nanomechanical properties of EPS adhesive fibres . However, as yet there has been no systematic, quantitative study of whole cell adhesion properties of different isolates or morphotypes of P. tricornutum, nor whether they show differential adhesiveness in relation to surface wettability.…”
Section: Introductionmentioning
confidence: 99%
“…Similar reports were found that the presence of EPS led to a higher prevalence of viable diatom cells in the biofilm undergoing elevated or fluctuating salinities stress in marine environments. [34,35] Therefore, EPS appeared to be an important adaption which promoted population persistence for the diatom-biofilm.…”
Section: Discussionmentioning
confidence: 99%